Finite Element Model of Rock Obstruction on Overtopping at the Coastline - Marpaung, Rony Genevent; Tulus, Tulus; Mardiningsih, Mardiningsih (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Wave overtopping is a common phenomenon that occurs during extreme sea conditions, where water waves travel over the surface of an open structure towards the sea and pass over its crest. To prevent flooding and coastal erosion, rock structures are often constructed as wave barriers along the shore. These barriers serve as a solution to mitigate wave overtopping. One of the key factors influencing overtopping is the arrival of continuous and sufficiently high-water waves that can pass through the top of coastal defense structures. Several phase settlement methods have been developed and applied to analyze wave overtopping using the Navier-Stokes (NS) equation. By employing the finite element method, numerical solutions and simulations are sought by inputting specific parameter values. This process aims to validate the accuracy of the resulting mathematical model. To accomplish this, a program is developed based on the discretization of the model, enabling a system analysis approach. The obtained results exhibit minimal error values, thereby demonstrating optimal outcomes in terms of rock placement. The entire fluid mechanics system analysis is simulated using the COMSOL Multiphysics 5.6 program, which provides a comprehensive platform for studying and evaluating the performance of the wave barrier system